The problem of continuity of traditions in the work of contemporary Japanese writer (Eurasian Journal of Philology Science and Education, 2018)
In article consider the theoretical aspect of the major literary concepts «tradition» and «innovation» of the Japanese literature. In literature traditions and innovation constantly alternate. When there take place essential shifts in art systems, which are followed by discussions during transition from one literary period to another, the interrelation between traditions and innovation becomes intense. Literary process of present Japan is difficult and contradictory. And matter is not only in variety of streams, directions, styles, genres. Complexity, first of all, is explained by the fact that now in the Japanese literature writers of different generations work, the special vision of the world is peculiar to each of which, various understanding of social and spiritual problems of society, the ambiguous relation to the past, the present and the future of the country. Critics are most unanimous in assessment of works of those writers behind which there is a wide life and creative experience. Their works differs in extension of the image of reality, deep philosophical judgment of complex problems of the present, sense of responsibility to society.